Peran Orang Tua Terhadap Pencegahan Kekerasan Seksual Pada Anak di Sekolah Dasar - Dalman, Dalman; Hanafiah, Dinda Okta Bella; Yuni, Tri Rahma; Cahyanti, Nurul; Aldiyansyah, Muhammad; Fahrezi, Yesa Enjelia; Rahmadhani, Della Thesar; Dinata, Rian Jon (Civiliza Publishing, 2024)
This socialization is intended to provide an overview to parents at SD Negeri 1 Gisting Permai about their role in preventing sexual violence. This study uses the method of counseling analysis (initial, core, and final activities) in a qualitative descriptive approach. Parents and students of grades V and VI of SDN 1 Gisting Permai participated in this study. The findings of the study showed that every 6th grade student of SDN 1 Gisting Permai and their parents who attended the seminar responded well. This program is intended to provide an overview to parents at SD Negeri 1 Gisting Permai about their role in preventing sexual violence. This study uses the method of counseling analysis (initial, core, and final activities) in a qualitative descriptive approach. Parents and students of grades V and VI of SDN 1 Gisting Permai participated in this study. The findings of the study showed that every 6th grade student of SDN 1 Gisting Permai and their parents who attended the seminar responded well.